The frequency of Osgood-Schlatter disease in adolescence training football - Lewandowska, Anna; Ratuszek-Sadowska, Dorota; Hoffman, Jarosław; Hoffman, Anetta; Kuczma, Monika; Ostrowska, Iwona; Hagner, Wojciech (Journal of Education, Health and Sport, 2017)
Osgood-Schlatter disease is most often seen in adolescents in intensive growth. However, the disease is more common in males than females, which may have a bearing on the greater physical activity of boys. Since the onset of the disease, the symptoms resolve spontaneously in over 90% of patients in 12-24 months. Although the disease has been known for over 100 years, the cause of its origins has so far been raised by a number of doubts. The aim of the study was to obtain information on how often Osgood-Schlater disease occurs in adolescents who practice football and influence of the intensity of training on occurrence of this condition among young players. The research material was a group of 21 boys from 12-14 years of age training football. The study was conducted in the Pomeranian Football Club with the permission of parents and coaches. The survey techniques in their own construction was used to answer the question of how often sterile tibial necrosis of tibia in boys training football occurs. Analysis of the collected data showed that the intensity of training did not influence the occurrence of Osgood-Schlatter disease. Rehabilitation and correct attitude have a great impact on rapid recovery and prevent recurrence. The frequency of Osgood-Schlater’s disease in adolescence training football depends on many factors. The disease is most often seen in adolescents during rapid growth as confirmed by the results of the study.